A Globally Convergent Algorithm for a Locally Lipschitz Function (Journal of Computational Mathematics, 1991)
In this paper, an algorithm of global convergence is proposed for a locally Lipschitz function, which is strictly differentiable at almost all differentiable points, and several examples are computed on an IBM PC.